Potent hepatoprotective activity of common rattan (Calamus rotang L.) leaf extract and its molecular mechanism - Walaa S. Anwar; Fatma M. Abdel-maksoud; Ahmed M. Sayed; Iman A. M. Abdel-Rahman; Makboul A. Makboul; Ahmed M. Zaher (BMC, 2023)
Abstract Background Calamus rotang L. (CR) is an Indian shrub. The leaves and other organs of the plant are traditionally used in India for treatment of various diseases. The in vitro antioxidant property of the leaves extract was previously established. Thus, the current study aimed to evaluate the antioxidant and hepatoprotective effects of CR ethyl acetate extract at a dose of 350 mg/kg on CCl4 induced hepatotoxic rats through different mechanisms. Methods Histopathological examination of the treated rats' group in comparison with positive and negative controls were performed. Quantitative measuring of the proinflammatory cytokines (TNF α), inflammatory regulators (Arginase, PPAR α) and the antiapoptotic protein Bcl-2 in comparison with positive and negative control groups was achieved using immunohistochemical examination. HPLC profiling of the polyphenol contents and molecular docking of the identified compounds against BH3 proapoptotic protein were correspondingly studied to evaluate the potential antiapoptotic property. Results The CR extract greatly protects the liver tissue through the suppression of TNF α, arginase and PPAR α induced by CCl4 as well as its enhancement of the antiapoptotic Bcl-2 protein. Fourteen polyphenols of different classes were identified in CR extract and tested via molecular docking for their potential antiapoptotic activities against BH3 protein. Naringin, rutin, 7-hydroxy flavone, and ellagic acid compounds exhibit the highest affinity and potential inhibition of pro-apoptotic protein BH3 via molecular docking study. Conclusions The ethyl acetate fraction of the leaves of C. rotang is rich in polyphenols that exhibited potent hepatoprotective effect on CCl4 induced hepatotoxic rats through its antioxidant, anti-inflammatory, anti-steatosis and antiapoptotic properties.